2007
DOI: 10.1089/vbz.2007.0125
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Effects on Plague and Tularemia in the United States

Abstract: Plague and tularemia are serious zoonotic diseases endemic to North America. We evaluated spatial patterns in their transmission in view of changing climates. First, we tested whether observed shifts since the 1960s are consistent with expected patterns of shift given known climate changes over that period. Then, we used general circulation model results summarizing global patterns of changing climates into the future to forecast likely shifts in patterns of transmission over the next 50 years. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 42 publications
4
82
0
2
Order By: Relevance
“…The SOI, computed from fluctuations in the surface air pressure difference between Tahiti and Darwin, Australia, 26 It had been shown that ENSO was associated with other vector-borne diseases and zoonoses, such as malaria, 38,39 dengue fever, 40,41 Ross River virus infection, 42,43 cutaneous leishmaniasis, and plague. 44,45 Similarly, our results indicate that in addition to relative humidity and maximum temperature, SOI is also associated with HFRS incidence in Heilongjiang Province. Thus, local climate (e.g., temperature and humidity) was more likely to directly affect life cycle dynamics (e.g., reproductive rates and incubation periods) of the disease agents themselves, whereas largerscale factors (e.g., SOI) could also influence broader ecologic processes and have possibly nonlinear impacts on disease transmission dynamics.…”
Section: Discussionsupporting
confidence: 67%
“…The SOI, computed from fluctuations in the surface air pressure difference between Tahiti and Darwin, Australia, 26 It had been shown that ENSO was associated with other vector-borne diseases and zoonoses, such as malaria, 38,39 dengue fever, 40,41 Ross River virus infection, 42,43 cutaneous leishmaniasis, and plague. 44,45 Similarly, our results indicate that in addition to relative humidity and maximum temperature, SOI is also associated with HFRS incidence in Heilongjiang Province. Thus, local climate (e.g., temperature and humidity) was more likely to directly affect life cycle dynamics (e.g., reproductive rates and incubation periods) of the disease agents themselves, whereas largerscale factors (e.g., SOI) could also influence broader ecologic processes and have possibly nonlinear impacts on disease transmission dynamics.…”
Section: Discussionsupporting
confidence: 67%
“…Our results emphasize the importance of selecting the most appropriate and informative environmental data for ecologic niche modeling. Models based on simple environmental data sets may be overly general and lacking detail, owing to the broad interpolation and smoothing inherent in the process of generating the climate coverages (Nakazawa et al, 2007). Refinements such as filtering occurrence localities based on spatial precision can avoid imprecision resulting from an uncertain geolocation (Wieczorek et al, 2004;Peterson, 2008b).…”
Section: Diseases and Niche Modelingmentioning
confidence: 99%
“…Trends related to increased climatic variability and intensity (Karl et al 2009) due to global climate change are a concern because these factors could exacerbate vector-borne disease outbreaks by affecting a vector's life cycle and improve opportunities for pathogen survival and transmission (Githeko et al 2000, Patz et al 2005. Changing climatic trends may increase the likelihood that F. tularensis will impact new geographic locations (Nakazawa et al 2008).…”
Section: Introductionmentioning
confidence: 99%